SEX, MARITAL STATUS AND YEARS OF EXPERIENCE AS CORRELATES OF STRESS AMONG ACADEMIC STAFF IN SOUTH WEST NIGERIA - Omoniyi, Mary Banke Iyabo; Ongunsanmi, Joyce Olufunke (European Scientific Journal, ESJ, 2012)
This study investigated the level of perceived stress among Nigeria University Academic Staff in the South West based on the variables of sex, marital status, and years of experience as lecturers. The 364 subjects (223 males and 141 females) were selected from eight (8) universities (three (3) federal, three (3) state and 2 private). The stratified random sampling technique was adopted in selecting the subjects according to the population of lecturers in each university. The survey research design was adopted. A self Report perceived stress Assessment Questionare (SRPSAQ) constructed by the researchers was used to elicit information from the respondents. The instrument was made up of two (2) sections a and B. Section A consists of items based on the lecturers’ bio-data while section B contained various stress precipitating items to which subjects were to either strongly agree (4), agree (3), disagree(2) or strongly disagree (1). The face and content validities of the instrument were ensured while it’s reliability was ascertained through a test-re-test method with a reliability coefficient of 0.86. Three (3) null hypotheses were raised to guide the study. The data collected were subjected to appropriate descriptive (means and standard deviation) and in inferential (t-test) statistics. The result indicated that there is no significant difference in the level of stress perceived by male and female lecturers irrespective of their years of experience as lecturers. The findings, also revealed that there is no significant difference in the level of perceived stress by married and divorced lecturers. However there is a significant difference between the level of stress perceived by married and single lecturers. The findings were discussed and counseling implications were made for possible options to reduce stress among academics in the south west.